Role of Silver Diamine Fluoride in Dentistry - Khurshid, Zohaib; Shabbir, Juzer; Al-Otaibi, Abdullah Khaled; Alsalem, Abdulelah Mohammad; Alhamdan, Abdulmalik Abdullah; Jouhar, Rizwan; Ahmed, Muhammad Adeel (European Dental Research and Biomaterials Journal, 2020)
Dental caries is the most prevalent disease in primary, mixed, and permanent dentition. Many preventive and treatment strategies were used in the last decades. Silver diamine fluoride (SDF) is a promising nontoxic material which proves to be a turning point concerning conservative dentistry if the patient and dental practitioners are adequately educated regarding it. Several advantages have been reported related to the use of SDF, including the procedure being pain-free and drill-free, patient- and doctor-friendly caries control strategy, and management of dentinal hypersensitivity.
Keywords: dental caries; silver; fluoride; staining; arresting caries